A study to assess the knowledge, attitude, and practice on occupational blood and body fluid spill management awareness among nursing students in a tertiary care hospital in Chennai, Tamil Nadu - Vidhyashree, MD; Ramasubramanian, R; Dharaneswari, H (Asian Journal of Medical Sciences, 2022)
Background: Nurses form a major taskforce of healthcare providers in hospitals and are hence at a great risk of such exposure. Occupational exposure in the context of this study is the exposure of skin to blood and body fluids. Transmission of these infections puts healthcare providers at major risk. Proper decontamination and taking measures to prevent occupational exposure to blood, mercury and body fluids is a primary method of prevention of disease in a healthcare setup. Aims and Objectives: To estimate, the level of knowledge, attitude& practice of nursing students regarding the management of blood and body fluid spill. Methodology: A Cross sectional –KAP among Second and third years from Nursing school, Chennai. Result: Among 98 nursing students, second year nursing 40%, 61%, 40 % shows knowledge, attitude and practice respectively. Third year students shows better than second year which was 57%, 71%, 71 % shows knowledge, attitude and practice respectively. The studied participants had a median (IQR) percentage KAP score of 8(7-9) and 11 (10-13) for second and third year students respectively. Comparison KAP score of the excellent and fair among second and third year students showed the significant p-value (<0.001*) by the Mann- Whitney U test. Conclusion: Majority of third year nursing students showed better KAP than second year students hence we recommend more mock training classes to improve the knowledge and practice.